Improving self-efficacy in musical performance using socratic dialogue - Imanuel Ezra (Fakultas Psikologi, 2019)
This research try to investigate the effect of promoting self-efficacy to musical performance in a student, which had been done by explaining the student about the concept of self-efficacy, and a series of Socratic dialogue. This educational intervention was done to a junior high school student (X). Pre and post intervention measuring test were done using Pintrich and Groot’s Motivated Strategies for Learning Questionnaire (1990) that had been adapted to suit the context of music education. This study found that improving self-efficacy level in a student using Socratic Dialogue does have positive effect on musical performance and practice